Biochar: An Effective and Green Adsorbent for Hazardous Pollutants - Arshi Rastogi (Novel Aspects on Chemistry and Biochemistry Vol. 2, 2023)
To solve the water issue, novel wastewater treatment methods are required. The goal of scientists is to create a cheap, simple, and eco-friendly substance to remove pollutants. The use of biochar made from biowaste might perhaps solve the issue of water contamination. The main aim of this chapter is to discuss numerous facets of biochar, such as its sources, characteristics, adsorption mechanism, and uses, particularly in the context of wastewater treatment. Given its unique chemical composition, high porosity, and long-lasting stability, biochar has a lot of potential as a wastewater treatment material. Biochar has grown in importance as environmental degradation persists to worsen and scientists struggle to address contaminants.